Liquidity Risk Management in Islamic Banks: Issues and Challenges - Bello, Nabil; Hasan, Aznan (2016)
The purpose of this paper is to discuss the issues and challenges of liquidity risk management in Islamic banks. It also analyzes the meaning of liquidity risk, the sources of liquidity risk in Islamic banks and the common instruments used by Islamic banks to manage liquidity mismatches at both sides of their balance sheets. Secondary sources from existing literature was used to explain concepts and how they interrelate in the context of Islamic banks. The paper finds that Islamic liquidity management is an important building block for stable and efficient banking. Even though there are several attempts to find solutions to the incessant problems of liquidity faced by majority of Islamic banks, there are still several underlying problems in terms of deficiency in infrastructure especially in countries where Islamic finance is still infant, limitation of instruments and Shari’ah restrictions on some instruments. The study was limited to secondary sources without focusing on any location. Further case study in the areas where Islamic banking is suggested to further understand the dimensions of the problem. Regulatory bodies should come up with more innovative practices of Islamic liquidity management to solve unresolved theoretical issues and also meeting market requirements for liquidity. The paper presents the concept of liquidity risk management in the context of Islamic banking.